UPAYA PENGEMBANGAN E-GOVERNMENT PADA DINAS PENDIDIKAN PEMUDA DAN OLAHRAGA KOTA - Darmajaya Darmajaya (UNIVERSITAS INDO GLOBAL MANDIRI, 2019)
This study aims to: To determine the extent to which efforts to develop e-government that has done the Dinas Pendidikan Pemuda dan Olahraga Palembang, and what aspects are the supporters and the inhibitor in these efforts. Perspective approach used in this study is qualitative research, research that retrieve data using interviews as a means of collecting primary data. Based on the interview can be drawn the following conclusions: Effort has been the Dinas Pendidikan Pemuda dan Olahraga Palembang in developing e-government, new limited provision of infrastructure, application systems, and training of human resources, and the aspects of the support in these efforts, among others, the Department Head will provide a budget to build e-government, and a commitment to providing the best service, fast and vibrant to the community, and than aspects that become an obstacle in these efforts, among others, human resource capacity to manage e-government is very limited, yet not used to document all existing activities, and application development of existing systems are still shaped islands that are not yet integrated applications from each other . Keywords : Efforts to Develop E-Government